IMPLEMENTASI KEBIJAKAN PROGRAM TANGGAP KARAWANG OLEH DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KARAWANG: Array - Elda Riani; and (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Research is intended to find out how the implementation of the Karawang Response Program carried out by the communication and information officer of the Karawang district, to accommodate and settle any existing issues in society through public complaints. The method used was to use a descriptive method with a qualitaitive, narrative approach. The resulting data include primary data coming from the informant directly and secondary data coming from other data support. The study is conducted by direct observation, in-depth interviews of supportive sources and instrument reinforced by documentation and is supported by secondary data available. Studies have shown that the implementation of the Karawang Response Program (Tangkar) is good, even throught teh implementation of it still has several flaws in it. Such as a direct lack of socializing of the community and a lack of support facilities like a free internet network for the community.